Improving quality of life through self-care practices in type 2 diabetes mellitus patients: A Cross-sectional study - Harbaeni Harbaeni; Hasniati Hasniati; Pramadhita A.P. Botutihe (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic condition requiring sustained self-management to prevent complications and maintain quality of life. Despite increasing prevalence, evidence on how self-care behaviors influence patient-reported outcomes in primary care settings remains limited. This study aimed to examine the association between self-care practices and quality of life among patients with T2DM. Research Methodology: A quantitative cross-sectional study was conducted at Cendrawasih Health Center, Makassar, Indonesia, from June to September 2023. A total of 266 participants were selected using purposive sampling. Data were collected using the WHOQOL-BREF and Self-Care Activity Scale. Descriptive statistics and chi-square tests were performed, followed by logistic regression to estimate adjusted odds ratios (AOR) with 95% confidence intervals. Results: Most respondents demonstrated good self-care (98.5%) and very good quality of life (96.6%). Bivariate analysis showed a significant association between self-care and quality of life (p < 0.001; C = 0.489). In multivariate analysis, good self-care was strongly associated with higher odds of a very good quality of life (AOR = 12.85; 95% CI: 2.10–78.60; p = 0.005), after adjusting for age, sex, duration of diabetes, and education level. Conclusion: Self-care practices are a strong and independent determinant of quality of life in T2DM patients. Strengthening structured self-management education, continuous monitoring, and community-based support systems is essential to improve patient outcomes. Integrating behavioral and health system interventions may enhance sustainable diabetes management.